Optimizing Contrast Resolution in Digital Chest Radiography by Varying Copper Filtration and kVp. - Balac, Vesna; Grossman, Robert; Griswold, Randy; Bowman, Dennis (Radiologic Technology)
Purpose To measure the effect of increasing kilovoltage peak (kVp) and copper filtration thickness on entrance skin exposure and contrast resolution for chest radiography performed using digital flat-panel detectors. Methods A phantom-based experiment was conducted in which 24 radiographs of a quality control chest phantom were obtained at varying kVp levels and copper filtration thicknesses. The entrance skin exposure was measured and analyzed for each exposure. All radiographs were analyzed based on measured pixel values and contrast:noise ratio (CNR) and using subjective analysis, which focused on contrast resolution assessment performed by 4 radiologists. Results The results from the subjective image analysis showed that increasing copper filtration in increments of 0.1 mm resulted in less of a decrease in contrast resolution compared with increasing the kVp by 10 kVp, and that contrast resolution is more dependent on energy level than on filtration. The results from objective image analysis indicated that CNR decreased when kVp increased at all filtration thicknesses, but consistent dependency between CNR and filtration was not evident. Exposure data analysis showed an average 46% decrease in entrance skin exposure for each increase of 0.1 mm in copper filtration thickness. Discussion Although subjective and objective data analysis results indicated that increases of copper filtration are more beneficial to maintaining contrast resolution and reducing entrance skin exposure compared with increases of kVp, objective image data analysis showed a greater reduction in contrast resolution when kVp is increased. These results validate previous research that concluded that copper filtration should be considered as a dose-reduction and imageoptimization strategy in digital radiography departments. Conclusion Although entrance skin exposure reduction can be accomplished using higher kVp and copper filtration, increasing copper filtration thickness could be considered to minimize the loss of contrast resolution for routine chest imaging when digital flat-panel detectors are used.